Institutional stepping stones for democracy: how and why multipartyism enhances democratic change. Issue 1 (2nd January 2018) - Teorell, Jan; Wahman, Michael
ABSTRACT: Scholars of electoral authoritarianism and comparative institutions have emphasized how authoritarian regimes implement multiparty elections to stabilize authoritarian rule and diffuse political opposition. Consequently, the literature has advised against the notion that multiparty elections constitute a general lever for democratization. This article presents evidence in support of a more positive understanding of multipartyism and democracy. We argue that multiparty elections create an institutional space for oppositional parties, instrumentally motivated to promote further positive democratic change. We hypothesize that multiparty regimes are (1) generally more likely to experience positive democratic change, and (2) more importantly, more likely to do so when faced by internal or external regime threats. We test these hypotheses using cross-section time-series data on 166 countries in the period 1973–2010. Our results show a general positive effect of multipartyism for democratic change, and that multiparty regimes are more likely to improve their levels of democracy when faced with demonstrations and economic crisis.